2012
DOI: 10.1007/s11033-012-1597-9
|View full text |Cite
|
Sign up to set email alerts
|

IFN-gamma and IL-12B polymorphisms in women with cervical intraepithellial neoplasia caused by human papillomavirus

Abstract: The Human Papillomavirus (HPV) is a sexually transmitted organism associated with Cervical Intraepithelial Neoplasia (CIN) and cervical cancer, the second main cause of malignancy in women worldwide. The virus itself, however, is not enough to cause lesions on the cervix. Several studies suggest that some polymorphic sites changes the cytokines levels and influence the cancer development in HPV infected patients. In this study, we evaluated the presence of functional polymorphisms at +874 (T/A) IFNG and +1188 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…We also excluded two articles on cervical intraepithelial neoplasia [9,16], and the significance of pooled ORs did not change. Five articles with scores of quality score assessment ≥10, which was considered Bhigh-quality^studies, were performed in a pooled analysis, and the results indicated no significant difference from the overall meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We also excluded two articles on cervical intraepithelial neoplasia [9,16], and the significance of pooled ORs did not change. Five articles with scores of quality score assessment ≥10, which was considered Bhigh-quality^studies, were performed in a pooled analysis, and the results indicated no significant difference from the overall meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the search terms, 20 articles were identified; one article was hand-searched, 13 articles were excluded according to the inclusion and exclusion criteria, and finally, eight articles including nine studies with 1,116 cases and 1,290 controls were identified as suitable for a meta-analysis [9][10][11][12][14][15][16][17] (Fig. 2).…”
Section: Literature Selection and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations